Biodiversity Study on Various Land Uses in Jatiarjo Village, Pasuruan Regency - Muhammad Ramdhan Kalandoro Wardoyo; Bakti Wisnu Widjajani; Fitri Wijayanti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Biological diversity is part of the ecological chain within the environment or ecosystem. The interrelationship among all living organisms, including microorganisms, flora, and fauna, cannot be overlooked. Biological diversity is often used as an indicator of ecosystem health. Biodiversity can be measured using the biological diversity index introduced by Shannon and Wiener, which serves as a reference for evaluating diversity levels. This research aims to examine existing biological diversity. The study uses the Shannon–Wiener method, which is commonly used to measure species diversity within communities across various land-use types, including Garden Mix 1, Garden Mix 2, fields, and gardens. Each land-use type possesses different vegetation diversity characteristics. Garden Mix 1 combines woody plants and horticultural crops, whereas Garden Mix 2 features a mix of horticultural plants and shrubs. The results of this research may serve as a recommendation and as a foundation for further sustainable studies, such as carbon stock research and biodiversity assessments.